Hepatitis B virus persistence in mice reveals IL-21 and IL-33 as regulators of viral clearance - Zhongliang Shen (Nature Portfolio, 2017)
Hepatitis B virus (HBV) establishes chronic infection in only some patients, but the mechanisms underlying clearance failure in these patients are not fully understood. Here, the authors identify and characterize an HBV strain that can persist in mice and show that IL-21 and IL-33 responses contribute to clearance.